Synthesis and applicability study of novel poly(dopamine)-modified carbon nanotubes based polymer electrolyte membranes for direct methanol fuel cell. Issue 5 (October 2020) - Altaf, Faizah; Gill, Rohama; Batool, Rida; Zohaib-Ur-Rehman,; Majeed, Hammad; Abbas, Ghazanfar; Jacob, Karl
Graphical abstract: Highlights: Composite membranes based on polydopamine functionalized CNT and sulfonated polysulfone were fabricated successfully. Composite membranes exhibited efficient methanol permeability (5.68 × 10 −7  cm 2 /s) than Nafion®117 (23.00 × 10 −7  cm 2 /s). PCSPS0.5 composite membrane exhibits highest proton conductivity of 0.1216S/cm is observed at 80 °C. Abstract: Novel sulfonated polysulfone (SPS) based composite polymer electrolyte membranes (PEMs) filled with polydopamine modified carbon nanotubes (PD-CNTs) have been prepared using the phase inversion technique. The present study reports the development of novel and cost- efficient nanocomposite materials with excellent properties for polymer electrolyte membranes preparation. The progress is noteworthy towards the synthesis of economical organic-inorganic nanocomposites through which fuel cell related properties can be tailored. The applicability of prepared PEMs for direct methanol fuel cell (DMFC) has been investigated in terms of water uptake, methanol permeability, and proton conductivity by changing the filler content (0.5–1.0 wt. %). The carbon nanotubes were surface functionalized using polydopamine (PD) as the modifying agent. The resultant functionalized carbon nanotubes (PD-CNTs) have been incorporated into SPS polymer matrix to prepare the composite PEMs. The functional groups, structural properties, elemental analysis, morphological and topographical aspects of the resulting composite membranes were characterized using Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), Energy dispersive X-ray spectrometer (EDS), Scanning electron microscopy (SEM), and Transmission electron microscopy (TEM), respectively. It was found that PD served as an outstanding glue because of its adhesive qualities, facilitated the homogeneous dispersion of CNTs into the polymer matrix, and created new proton-conducting pathways in the subsequent membranes. A detailed analysis showed that water uptake and proton-conducting properties of the engineered PEMs have been improved significantly. Composite membarne (0.5 wt. % PD-CNTs) showed 43 % increase in proton conductivity compared to the pristine SPS membrane, increasing from 0.085 S/cm for pristin to 0.1216 S/cm for the composite membrane at 80 °C. The prepared PEMs also showed an impressive 75 % decrease in methanol permeability (5.68 × 10 −7  cm 2 /s) compared to recast Nafion®117 membarne (23.00 × 10 −7  cm 2 /s). These results demonstrated the immense potential of polydopamine functionalized CNTs based PEMs for DMFC application. The ability of the newly synthesized membrane to retain water, and its capability to give a structural framework for maximum proton conductivity with reduced fuel crossover towards the catalyst are the significant advances from the present study.